2015
DOI: 10.1371/journal.pone.0144850
|View full text |Cite
|
Sign up to set email alerts
|

Association between Retinal Arteriolar and Venule Calibre with Prevalent Heart Failure: A Cross-Sectional Study

Abstract: BackgroundThere is evidence to suggest that microvascular disease, particularly diabetic retinopathy, plays a role in the pathogenesis of HF. However, whether changes in retinal vessel calibre predicts HF is unclear. The purpose of this study was to examine the association of retinal microvascular structure with prevalent heart failure (HF).MethodsThe Australian Heart Eye Study (AHES) is a cross-sectional study that surveyed 1680 participants who presented to a tertiary referral hospital for the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
18
1
Order By: Relevance
“…The population‐based Australian Heart Eye Study (AHES) reported a significant association between wider retinal arterioles and prevalent HF, independent of the traditional risk factors . This association appeared stronger in patients with diabetes compared with those without diabetes . In contrast to the present study by Chandra et al ., no association was observed between wider retinal venules and HF, for reasons that remain unexplained.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…The population‐based Australian Heart Eye Study (AHES) reported a significant association between wider retinal arterioles and prevalent HF, independent of the traditional risk factors . This association appeared stronger in patients with diabetes compared with those without diabetes . In contrast to the present study by Chandra et al ., no association was observed between wider retinal venules and HF, for reasons that remain unexplained.…”
contrasting
confidence: 99%
“…9 This association appeared stronger in patients with diabetes compared with those without diabetes. 9 In contrast to the present study by Chandra et al, 10 no association was observed between wider retinal venules and HF, for reasons that remain unexplained. In addition, in the same Australian cohort, no association was observed between the magnitude of age-related macular degeneration and prevalent HF.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…As we all know, hypertension can cause small vascular lesions throughout the body, especially the retinal vessels. Recently, many studies have already investigated in the relationship between HCY and cardiovascular or cerebrovascular diseases [1][2][3]. Retinal vessels are the only visible microvascular in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a close attention was paid on the retinal microvasculature [2] and it's visualization in patients with CVD [3][4][5][6][7][8]. The retina is the only place in whole human organism, where are visible vessels of alive person, reflecting early changes in other organs.…”
mentioning
confidence: 99%